2004
DOI: 10.1152/ajpendo.00539.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia and the sympathoadrenal system: neurogenic symptoms are largely the result of sympathetic neural, rather than adrenomedullary, activation

Abstract: The relative contributions of the sympathetic nervous system and the adrenal medullae, the two components of the sympathoadrenal system, to the manifestations of hypoglycemia are largely unknown. We tested the hypothesis that the neurogenic symptoms of hypoglycemia are largely the result of sympathetic neural activation. To do so, we quantitated neurogenic symptoms, as well as norepinephrine (NE) kinetics and selected hemodynamic changes, during hyperinsulinemic euglycemic and stepped hypoglycemic clamps in 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 32 publications
3
62
0
2
Order By: Relevance
“…The relative amounts of W, NREMS and REMS on the baseline day from 30-120 minutes after saline injection are comparable to a recent sleep study from our laboratory conducted from 1300-1500 hours that did not involve subcutaneous injections [26]. Although a hyperinsulinemic, euglycemic group was not included in this study, we believe that the effect of insulin treatment on arousal reported here is due to hypoglycemia, rather than hyperinsulinemia, for the following reasons: 1) Hyperinsulinemic euglycemic clamp studies in normal humans are not associated with significant autonomic activation or development of hypoglycemic symptoms [27]. 2) In the study of Banarer and Cryer, altered sleep efficiency during stepped hypoglycemic clamp was not reported for non-diabetic humans studied at the 85, 75, or 65 mg/dl steps, only during the 55 and 45 mg/dl steps [14].…”
Section: Discussionsupporting
confidence: 73%
“…The relative amounts of W, NREMS and REMS on the baseline day from 30-120 minutes after saline injection are comparable to a recent sleep study from our laboratory conducted from 1300-1500 hours that did not involve subcutaneous injections [26]. Although a hyperinsulinemic, euglycemic group was not included in this study, we believe that the effect of insulin treatment on arousal reported here is due to hypoglycemia, rather than hyperinsulinemia, for the following reasons: 1) Hyperinsulinemic euglycemic clamp studies in normal humans are not associated with significant autonomic activation or development of hypoglycemic symptoms [27]. 2) In the study of Banarer and Cryer, altered sleep efficiency during stepped hypoglycemic clamp was not reported for non-diabetic humans studied at the 85, 75, or 65 mg/dl steps, only during the 55 and 45 mg/dl steps [14].…”
Section: Discussionsupporting
confidence: 73%
“…However, our data are consistent with other studies in which hormonal responses and awareness have not been concordant and provide further evidence that adrenaline responses per se do not define hypoglycaemia unawareness [e.g. 46,47].…”
Section: Discussionsupporting
confidence: 92%
“…The origin of hypoglycemic symptoms during hypoglycemia is complex. Previous studies demonstrated scenarios whereby discordant responses between autonomic symptoms and catecholamine responses can exist during hypoglycemia (17,(31)(32)(33). Generally, studies have determined that autonomic symptoms can be preserved despite reduced activity in other branches of the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, studies have determined that autonomic symptoms can be preserved despite reduced activity in other branches of the sympathetic nervous system. For example, DeRosa et al (31) demonstrated that symptom responses are preserved in adrenalectomized subjects who have no measurable epinephrine levels during hypoglycemia. Additionally, Aftab-Guy et al (34,35) demonstrated that high levels of plasma epinephrine mimicking values observed during moderate hypoglycemia only produce minor increases in hypoglycemic symptoms.…”
Section: Discussionmentioning
confidence: 99%